Family reunification within the refugee context: Is South Africa meeting its International, regional, constitutional and legal obligations towards refugees? - Khan, Fatima (Department of Private Law, 2023)
The refugee experience is such that it is common for family members to be separated from each other before or during their flight from the country of origin. In the face of persecution, families adopt strategies, some of which may necessitate temporary separation: sending a politically active adult into hiding, helping a son escape forcible recruitment by militia forces, sending abroad a woman at risk of attack or abduction. Family members may be forced to take different routes out of the country or to leave at different times as opportunities permit. It is therefore also common for refugees to be unaware, often for long periods, whether a family member is alive or dead. The commonality of the experience does not in any way detract from the pain and anxiety felt by those separated from close family members.